Age grading or language change? On young Norwegians and English influence - Sunde, Anne Mette (Målbryting, 2025)
The article discusses the role of young Norwegians in the influence of English on the Norwegian language. It is commonly assumed that young Norwegians use a more English-influenced variety than older generations, and that they are at the forefront of the anglicization of Norwegian. However, an interesting question is whether the use of English among youth represents the beginning of language change, or whether it is rather a life-stage phenomenon tied to adolescence and early adulthood. I argue that young age plays a relatively minor role, and that the extent of anglicized language use is more closely linked to lifestyle factors and language attitudes commonly found among young people. Furthermore, I suggest that whether anglicisms are abandoned with age or retained and contribute to long-term changes in Norwegian partly depends on the type of anglicism. Anglicisms with a foreign form (typically loanwords) are assumed to be more conscious forms that are easy to avoid using, while anglicisms with a domestic form (typically calques) are assumed to be less conscious and therefore harder to discard during the transition to a new life-stage. The article draws on recent linguistic data from social media platforms – a type of material that has so far received little attention in the Norwegian context. In this way, the article also highlights the potential role of social media in language change, and how today’s media landscape may facilitate increased use of English.
Keywords: age-graded variation; anglicisms; English influence; borrowing; code-switching; language change; youth language